Capturing coaches' identity leadership within youth sport. (July 2022) - Herbison, Jordan D.; Sutcliffe, Jordan T.; Martin, Luc J.; McLaren, Colin D.; Slatcher, Richard B.; Benson, Alex J.; Boardley, Ian D.; Côté, Jean; Bruner, Mark W.
Abstract: The social identity approach discusses leadership as a repetitive and multi-dimensional group process relying on leaders' abilities to represent, advance, create, and embed a shared sense of social identity amongst their followers (Haslam, Fransen, & Boen, 2020). Purpose: To conduct an in-depth exploration of youth coaches' use of identity leadership in a naturalistic setting. Methods: The Electronically Activated Recorder was used to sample and record conversations between eight head coaches ( M age  = 44.88 years, SD  = 6.08; M experience  = 11.25 years, SD  = 6.18) and members of their teams, other teams, and officials during a three-day competitive youth ice hockey tournament in Central Ontario, Canada. A total of 597 audio observations captured coaches' sport-related conversations at the tournament. We followed Fletcher's (2017) analysis guidelines involving the identification of preliminary trends or patterns in the data, theoretical redescription, and contextual considerations. Results: Coaches' conversations aligned with the four principles of identity leadership, and thus the observational data were organized into the higher-order themes of identity prototypicality, advancement, entrepreneurship, and impresarioship. The findings illuminate the potential of identity leadership to promote and undermine youth athletes' positive experiences in sport. Conclusion: Coaches engaged in identity leadership behaviors in a variety of social environments (e.g., car ride to/from competition, locker room, during competition). The findings provide new details about identity leadership in practice and caution its potential to undermine positive athlete experiences in youth sport. Highlights: Youth coaches' conversations observed using the Electronically Activated Recorder. Findings demonstrate use of identity leadership in youth coaches' daily behaviors. Illustrates positive and negative applications of identity leadership. Youth coaches use identity leadership before, during, and after competition.